A systematic review of social classroom climate in online and technology-enhanced learning environments in primary and secondary school - Goagoses Naska; Suovuo Tomi; Winschiers-Theophilus Heike; Suero Montero Calkin; Pope Nicolas; Rötkönen Erkki; Sutinen Erkki (Springer New York LLC, 2025)
Although the significance of a positive social classroom climate in face-to-face learning has been established, its role within online and technology-enhanced learning environments is unclear. The central aim of this systematic review was to synthesize the findings of empirical studies which have examined any aspect of the social classroom climate in online and technology-enhanced learning environments in primary and secondary schools. Appropriate search terms were entered into ACM Digital Library, Web of Science, Scopus, and ERIC in November 2021. Articles were included if they were relevant for the aim, reported primary data, sampled primary/secondary school students and/or teachers, and were published in journals, conference proceedings, or book chapters in English. Furthermore, articles were excluded if they focused on the development/testing of measurement tools. The thematic narrative synthesis includes 29 articles, comprising of qualitative, quantitative, and mixed-method studies. A quality assessment checklist was completed for all. The findings encompass examinations of the social classroom climate in online learning before and during the Covid-19 pandemic, in blended learning environments and a comparison between them. Furthermore, associations between the online social classroom climate and academic variables is explored, as is the fostering thereof through synchronous/asynchronous discussion groups and social media. We discuss the theoretical framing of the studies, the impact of a positive classroom climate in online and technology-enhanced learning environments on students, as well as practical approaches and new opportunities in leveraging technologies. Based on the findings and the studies’ limitations we outline implications and future research, such as the need to consider students’ voices and diversity, technology perspectives, a transdiciplinary approach and the reconceptualization of boundaries.